Multipoint Boundary Conditions for Differential Operators - Valitskii, Yu. N.; Golets, B. I.; Zelenyak, T. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish differential properties of generalized solutions of multipoint boundary-value problems for ordinary differential equations.